The solution (x, y) = (3, -2)
Step-by-step explanation:
y = -x + 1
y = 2/3x - 4
Using the equal method:
we would equate both equation together. This because they are both equal to y
y = y
-x + 1 = 2/3x - 4
![\begin{gathered} -x+1=(2)/(3)x-4 \\ \text{add x to both sides:} \\ -x\text{ + x }+1=(2)/(3)x+x-4 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2l6sf2z20pn46j5zgria96t9i4bcbzoepu.png)
![\begin{gathered} 0+1=(2x+3(x))/(3)-4 \\ 1\text{ = }(5x)/(3)-4 \\ \text{add 4 to both sides:} \\ 1+4\text{ = }(5x)/(3)-4+4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/swzgwwem8q655grea2w0btw47rd37c8s57.png)
![\begin{gathered} 5\text{ = }(5x)/(3)+0 \\ (5)/(1)\text{ = }(5x)/(3) \\ cross\text{ multiply}\colon \\ 5(3)\text{ = 5x} \\ 15\text{ = 5x} \\ \text{divide both sides by 5:} \\ \frac{15}{5\text{ }}=\text{ }\frac{\text{5x}}{5} \\ 3\text{ = x} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/66htaayaxwc9sjflea5ozdclm67b9vgji4.png)
We replace x in any of the equation with 3 to get y:
using the first equation: y = -x + 1
y = -3 + 1
y = -2
The solution or the point of intersection (x, y) = (3, -2)